Pre-PCR Processing Strategies for Quantitative Detection of Food-Borne Pathogens using Real-Time PCR - Wolffs, Petra (Department of Applied Microbiology, Lund University, 2003)
Since the development of real-time PCR, the technology has been widely applied in the field of diagnostics. In comparison with conventional PCR it has opened up the possibility of accurate quantification of microorganisms in clinical, environmental and food samples. When employing real-time PCR and absolute quantification in biological samples, five important requirements should be fulfilled, namely (i) elimination of PCR inhibition, (ii) concentration of target nucleic acids or cells, (iii) conversion of heterogeneous samples into homogeneous PCR samples, (iv) avoidance of false-positive and false-negative results, and (v) enabling quantification. The objective of the work described in this thesis was to develop new pre-PCR processing strategies for quantification of pathogens in food, by altering the real-time PCR mixture and combining this with suitable sample treatment methods. The PCR mixture was modified by using alternative DNA polymerases and amplification facilitators to circumvent DNA inhibition and to obtain a good amplification efficiency. Furthermore, a new salt-insensitive probe system, based on a peptide nucleic acid thiazole orange conjugate, was studied. The resulting improvements in the PCR mixture were combined with a novel form of sample treatment called floatation which, in combination with quantitative (q) PCR, was used for absolute quantification of Yersinia enterocolitica and Campylobacter spp. in various food and clinical samples. Results showed that after floatation the sample matrix and the background flora could be separated from the target pathogen in such a way that PCR inhibition was minimized to levels comparable to that of purified DNA in Millipore water. Applying floatation to meat juice samples containing natural background flora and spiked with different concentrations of Y. enterocolitica, showed that absolute quantification of Y. enterocolitica was possible down to levels of 4.2 „e 103 CFU/ml even if an additional 1 ¡Ñ 106 CFU/ml BGF were added. Furthermore, the design of the floatation set-up ensured that false-positive results from free target DNA or dead cells were greatly reduced.
Article: I. Petra Wolffs, Rickard Knutsson, Robert Sjöback and Peter Rådström 2001. PNA-Based Light-Up Probes for Real-Time Detection of Sequence-Specific PCR Products. Biotechniques 31:766-771 Article: II. Peter S. Lübeck, Petra Wolffs, Stephen L.W. On, Peter Ahrens, Peter Rådström and Jeffrey Hoorfar. 2003. Towards an International Standard for PCR-Based Detection of Food-Borne Thermotolerant Campylobacters: Assay Development and Analytical Validation. Applied and Environmental Microbiology 69 (9):5664-5669 Article: III. Petra Wolffs, Halfdan Grage, Oskar Hagberg and Peter Rådström. Impact of DNA Polymerases and Their Buffer Systems on Quantitative Real-Time PCR. Journal of Clinical Microbiology. Accepted for publication. Article: IV. Petra Wolffs, Rickard Knutsson, Börje Norling and Peter Rådström. Rapid Quantification of Yersinia enterocolitica in Pork Samples Using a Novel Sample Preparation Method, Floatation, Prior to Real-Time PCR. Journal of Clinical Microbiology. Accepted for publication. Article: V. Petra Wolffs, Börje Norling and Peter Rådström Circumventing Risks of False-Positive Quantitative Real-Time PCR Results, Due to Detection of DNA Originating from Dead Cells. Submitted for publication. Article: VI. Petra Wolffs, Börje Norling, Peter S. Lübeck, Jeffrey Hoorfar and Peter Rådström. Quantification of Culturable and Viable Non-Culturable Campylobacter spp. from Chicken Rinse using Floatation prior to PCR. Manuscript.
Keywords: Livsmedelsteknik; Food and drink technology; DNA polymerase; sample treatment; pre-PCR processing; real-time PCR; Food-borne pathogens